Gatekeeping and the AEQ: An inside view - Edward W. Taylor (Adult Education Research Conference, 1993)
The Adult Education Quarterly publication activity from 1988-1992 was analyzed for gender and background (academic, practitioner, student) of authorship, geographic region of origin, type and subject of research and publication status. This analysis includes not only what was published, but all submitted manuscripts.